2017
DOI: 10.1155/2017/2105343
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Body Water Caused by Sleep Deprivation in Taeeum and Soyang Types in Sasang Medicine: Prospective Intervention Study

Abstract: Background There is a negative relationship between sleep deprivation and health. However, no study has investigated the effect of sleep deprivation on individuals with different body composition. The aim of this study was to determine the differential effect of sleep deprivation in individuals with different body compositions (fluid) according to Soyang type (SY) and Taeeum type (TE). Methods Sixty-two cognitively normal, middle-aged people with normal sleep patterns were recruited from the local population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In SCM, sleep is an important clinical indicator for the current health status and the assessment of interventions and prognosis; sleep states also vary across SC types [ 37 ]. Investigators of an experimental study [ 38 ], which limited sleep duration, reported that SY individuals are more sensitive to sleep restriction than TE individuals and have a slower recovery of body composition altered by sleep deprivation. Furthermore, poor sleep quality has been associated with obesity in SY and SE individuals [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In SCM, sleep is an important clinical indicator for the current health status and the assessment of interventions and prognosis; sleep states also vary across SC types [ 37 ]. Investigators of an experimental study [ 38 ], which limited sleep duration, reported that SY individuals are more sensitive to sleep restriction than TE individuals and have a slower recovery of body composition altered by sleep deprivation. Furthermore, poor sleep quality has been associated with obesity in SY and SE individuals [ 16 ].…”
Section: Discussionmentioning
confidence: 99%